2010
DOI: 10.1128/jb.00359-10
|View full text |Cite|
|
Sign up to set email alerts
|

Complete Nucleotide Sequence of TOL Plasmid pDK1 Provides Evidence for Evolutionary History of IncP-7 Catabolic Plasmids

Abstract: To understand the mechanisms for structural diversification of Pseudomonas-derived toluene-catabolic (TOL) plasmids, the complete sequence of a self-transmissible plasmid pDK1 with a size of 128,921 bp from Pseudomonas putida HS1 was determined. Comparative analysis revealed that (i) pDK1 consisted of a 75.6-kb IncP-7 plasmid backbone and 53.2-kb accessory gene segments that were bounded by transposon-associated regions, (ii) the genes for conjugative transfer of pDK1 were highly similar to those of MOB H grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 70 publications
0
29
0
Order By: Relevance
“…Such a divergence in the plasmid backbone genes within an Inc group (,80 % amino-acid sequence identity between homologues) has also been reported for the groups IncQ (Loftie-Eaton & Rawlings, 2012), IncP-9 (Sevastsyanovich et al, 2008) and IncX (Johnson et al, 2012), whereas relatively low divergence was observed among the currently available plasmid sequences of groups IncA/C (Fricke et al, 2009), IncI (Takahashi et al, 2011) andIncP-7 (Yano et al, 2010). Reduced similarity was observed, for an as yet unknown reason, specifically in a partitioning gene in IncI and IncP-7 groups despite high similarity in the replication and transfer genes within the Inc groups (Takahashi et al, 2011;Yano et al, 2010). This divergence in plasmid backbone sequence within a group of closely related plasmids may be the consequence of adaptive mutations that allow specialization towards specific bacterial hosts.…”
Section: Discussionmentioning
confidence: 96%
“…Such a divergence in the plasmid backbone genes within an Inc group (,80 % amino-acid sequence identity between homologues) has also been reported for the groups IncQ (Loftie-Eaton & Rawlings, 2012), IncP-9 (Sevastsyanovich et al, 2008) and IncX (Johnson et al, 2012), whereas relatively low divergence was observed among the currently available plasmid sequences of groups IncA/C (Fricke et al, 2009), IncI (Takahashi et al, 2011) andIncP-7 (Yano et al, 2010). Reduced similarity was observed, for an as yet unknown reason, specifically in a partitioning gene in IncI and IncP-7 groups despite high similarity in the replication and transfer genes within the Inc groups (Takahashi et al, 2011;Yano et al, 2010). This divergence in plasmid backbone sequence within a group of closely related plasmids may be the consequence of adaptive mutations that allow specialization towards specific bacterial hosts.…”
Section: Discussionmentioning
confidence: 96%
“…79) To date, in addition to pCAR1, complete nucleotide sequences have been reported for three other IncP-7 group plasmids: naphthalene degradative plasmid pND6-1, 80) toluene degradative plasmids pWW53, 81) and pDK1. 82) The replication and partition function regions of these plasmids were well conserved with that of pCAR1, and a 53.2-kb IncP-7 plasmid backbone was proposed based on a comparison of the nucleotide sequences. 82) Recently, seven IncP-7 naphthalene and salicylate degradative plasmids were also reported.…”
Section: Replication and Stable Maintenance Machinerymentioning
confidence: 99%
“…82) The replication and partition function regions of these plasmids were well conserved with that of pCAR1, and a 53.2-kb IncP-7 plasmid backbone was proposed based on a comparison of the nucleotide sequences. 82) Recently, seven IncP-7 naphthalene and salicylate degradative plasmids were also reported. 83) Thus IncP-7 plasmids are gaining importance as degradative plasmids.…”
Section: Replication and Stable Maintenance Machinerymentioning
confidence: 99%
See 2 more Smart Citations